Investigating the impact of customer satisfaction, trust, and quality of services on the acceptance of delivery services companies and related applications in Omani context: A Predictive model assessment using PLSpredict - Al-Madhagy Taufiq-Hail; Shafiz Affendi Bin Mohd Yusof; Ibrahim Rashid Humad Al Shamsi; Ermal Bino; Muhammad Saleem; Mudassar Mahmood; Hyder Kamran (Cogent Business & Management, 2023)
This paper investigates the impact of the COVID-19 pandemic on the adoption and evolution of delivery services in Oman. While the pandemic has presented new opportunities for delivery companies and related apps, there is a lack of research specifically focused on the Omani context. To address this gap, our study develops an integrated model based on the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB), incorporating additional variables to examine the role of customer satisfaction, trust, and service quality in the adoption of delivery services. Using a quantitative approach, we conducted a study involving systematic random sampling to collect responses from individuals with experience in using online purchase and delivery services. The model was evaluated using in-sample and out-of-sample prediction techniques, as well as measurement and structural analysis employing PLS-SEM. Our proposed model demonstrated strong predictive power and validity. The findings emphasize the significant contributions of service quality and trust to customer satisfaction. Furthermore, social influence emerged as a crucial factor influencing the intention to accept and adopt delivery services after experiencing satisfaction. The inclusion of PLSpredict analysis enhanced the reliability of our conducted analyses. This study provides original insights into the lessons learned from the global impact of COVID-19 and represents the first of its kind conducted in the Gulf Cooperation Council countries. Our research encourages further investigation of these topics in other GCC countries based on our findings. The study concludes by acknowledging its limitations, discussing theoretical and managerial contributions, and suggesting potential avenues for future research.
Keywords: 650; Acceptance and adoption; delivery services companies; e-retailer in Oman; PLSpredict analysis; quality of services; satisfaction; social influence; TAM and TPB integration; trust